Tumor extracellular matrix-targeted nanoscavengers reverse suppressive microenvironment for cocktail therapy - Chen, Xiaokai (2023)
Extracellular matrix (ECM) is not only a natural bulwark to shield solid tumor cells from therapeutic agents and cytotoxic T lymphocytes (CTLs), but also one of the key factors that cause tumor hypoxic environment, severely hindering photodynamic reactions and immune responses. In this work, multifunctional nanoscavengers (ECMT NS) consisting of digestive enzyme chymotrypsin, catalase, calcium peroxide nanoparticles, photosensitizer chlorin e6, and tumor ECM-targeting CLT1 peptide are rationally designed with several benefits for enhanced cocktail calcium ion/photodynamic/immune therapy. The scavengers can effectively “clear” tumor ECM via digestive proteolytic enzyme- and reactive oxygen species-mediated pathways, deepening tumor penetration of the scavengers and CTLs. Thanks to the ECM destruction and oxygen self-supply capability of ECMT NS, the hypoxia in tumors is attenuated, thus improving photodynamic therapeutic efficiency and downregulating immunosuppressive factors. Moreover, the combination of calcium ion overload and photodynamic therapy enriches damage-associated molecular patterns, which promotes CTL activation to inhibit abscopal tumor growth and lung metastasis. The presented ECM destruction strategy provides a solution to overcome the tumor suppressive microenvironment.